Resource use in whiteleg shrimp Litopenaeus vannamei farming in Ecuador. Issue 4 (4th June 2021) - Boyd, Claude E.; Davis, Robert P.; Wilson, Arturo González; Marcillo, Fabrizio; Brian, Susanna; McNevin, Aaron A.
Abstract: A survey of 101 shrimp farms in Ecuador revealed that the average annual shrimp yield based on production pond water surface area was 7.03 ± 0.93 (SE) t/ha/year. The range in annual yield among the five provinces with shrimp farms was 3.67 ± 0.71 to 11.95 ± 5.56 t/ha year, respectively. Averages for total land, water, and energy use were 0.54 ± 0.01 ha/t shrimp, 76, 817 ± 6, 330 m 3 /t shrimp, and 61.2 ± 4.2 GJ/t shrimp, respectively. Average wild fish use for fish meal and fish oil included in feed was 0.65 ± 0.02 t/t shrimp. One‐fourth of land use was land embodied in feed. Nearly 80% of total water use was incurred for exchanging water. Eighty‐seven of the farms practiced daily water exchange at an average rate of 8.5% pond volume per day (range 0.7–30%). Pumping water at all farms and mechanical aeration at 47 of the farms were the major direct energy uses. About half of the total energy use was embodied, and roughly half of the embodied energy was in feed.